Fabrication and Synthesis of Fluorescent Carbon Nanodots from Black Sticky Rice as Probes for detection Mg2+ ions - Ngara, Zakarias Seba; Mamut, Anastasia; Pingak, Redi Kristian; Johannes, Albert Zicko; Lerrick, Reinner Ishaq; Refli, Refli (Department of Chemistry, Faculty of Science and Technology Syarif Hidayatullah Jakarta State Islamic University, 2025)
Herein, fluorescent carbon nanodots (C-dots) with average diameter of 5.51 nm were fabricated from black sticky rice by using carbonization method. These C-dots have been synthesized with magnesium (Mg2+) ions to investigate their potential application as probes for detection Mg2+ ions. The as-obtained C-dots were measured their absorption (Abs), photoluminescence (PL), and FTIR spectra, X-ray diffraction (XRD) patterns and transmission electron microscopy (TEM) image. According to their Abs spectrum, the Abs peak at 276 nm confirmed the presence of C-dots in ethanol solution. Fortunately, the PL peak at 427 nm corresponded to their blue emission color. The XRD patterns and the TEM image confirmed also the formation of amorphous state and monodispersed spherical C-dots, respectively. When the as-prepared C-dots were synthesized with Mg2+ ions, the PL intensities of C-dots quenched as increasing the concentration of Mg2+ ions. A characteristic PL quenching of the C-dots through Mg2+ chelation demonstrated the sensing system up to the detection limit of 2.98 µM. This is the first reporting the application of C-dots as sensors for detection Mg2+ ions. These findings can pave the large opportunity for application of these C-dots in sensing, bioimaging, drug delivery, and so on.